Research on the Evaluation Methods of Microclimatic Impacts of Traditional Residential Architectural Layouts in Shenyang - Liu, Jiahao; Tanaka, Tomoyuki; Tan, Lei (International Journal of Natural Resources and Environmental Studies, 2024)
Urban environments are complex ecosystems where buildings, spaces, and human activities intertwine to influence the local climate, giving rise to what is known as the urban microclimate. This microclimate encompasses variations in temperature, humidity, wind patterns, and precipitation that occur in urban areas compared to their rural counterparts. These variations are not trivial; they significantly affect energy consumption, human comfort, and health, making the study of urban microclimates an essential aspect of sustainable urban planning [81]. The interplay between residential architecture and microclimatic conditions is a critical facet of urban environmental research. As cities grow, the configuration of built environments can significantly affect thermal comfort, air quality, and energy consumption, thereby dictating the liveability and sustainability of urban spaces. This study explores how specific residential layouts—row, diagonal, staggered gable, and enclosed—each manipulate air flow, sunlight exposure, and heat retention differently, contributing to varied microclimatic outcomes within urban neighborhoods.